Unraveling Sustainability: A Deep Dive into Adoption among Micro, Small, and Medium Enterprises - Muhammad Rizal; Farah Qalbia; Eka Wahyu Kasih (International Journal of Business, Marketing, Economics & Leadership (IJBMEL), 2024)
"Unraveling Sustainability: A Deep Dive into Adoption among Micro, Small, and Medium Enterprises" offers a comprehensive exploration of sustainability adoption within the MSME sector. Through empirical evidence, case studies, and expert insights, the book elucidates the motivations, challenges, and implications of sustainability practices among MSMEs. Key findings include the influence of external drivers such as regulatory pressures and market demands, as well as internal factors like organizational culture and leadership commitment, in shaping sustainability adoption. Moreover, the book highlights the role of government policies, organizational dynamics, and collaborative approaches in fostering sustainability within MSMEs. While providing valuable insights, the book acknowledges limitations in scope and generalizability, calling for further research to explore the long-term impacts and outcomes of sustainability practices on MSMEs. Overall, "Unraveling Sustainability" contributes to advancing understanding and promoting sustainable development within the MSME sector.